Implementasi Dan Evaluasi Aplikasi Inlislite Pada Perpustakaan SMA Bina Warga 2 Palembang - Wardah Miftahul Jannah; Irwansyah; Helda Yudiastuti; Kurniawan; Maria Ulfa (Jurnal Ilmiah Matrik, 2025)
The use of information technology has become an essential need and a reliable tool for solving various problems. In the education sector, information technology supports library services by improving efficiency, accessibility, and service quality. However, the library of SMA Bina Warga 2 Palembang has not fully utilized technology. Computers are used only in the laboratory for learning activities, while in the library they function solely for creating membership cards. Consequently, book circulation processes are still handled manually due to the absence of a database for recording borrowing and returning activities, which reduces data accuracy and security.This study aims to implement and evaluate the INLISLite application in the library. The Prototype method is used to enable direct interaction between developers and users during system development.The results indicate that the implementation of INLISLite improves the effectiveness and efficiency of library management processes